Effects of oven-dried ipil-ipil (leucaena leucocephala) leaves as feed component on the growth of broiler chicken. - Cacho, Nhel Kevin (UPHSI, 2006)
The country's poultry sector continues to be the forefront of the animal industries together with the swine sector. Chicken is one of the world's major and fastest sources of meat. Because of the high demand for chicken products, there is aggressive expansion, which coupled with high inputs in the local and international markets, results in diminishing returns and consequent losses to the poultry industry. Ipil-ipil is a potential feed additive under the family Leguminosae. This study was done to satisfy the following objectives: to determine the effects of oven-dried ipil ipil leaves as additive to commercial feed on growth rate based on live weight and to determine the percentage of oven-dried ipil-ipil leaves as additive to commercial feed that will yield the higest feed conversion rate and survival rate. and to determine the nutrient content of the experimental feeds. This study was used ipil-ipil leaves as assitive to commercial feed at percentages of 20%, 40%, 60%, and 80%. These were fed ad libitum to 22 days old AA70 breed boiler kitchen. Fresh water wih vitamins was also given everyday to ensure good health of the chickens. After 23 days of observation, results showed that the different feeds yielded both the highest growth rate based on live weight and higest conversion rate. However, the results of the 20% ipil-ipil leaves concentration is not significantly different from the results of the pure commercial feeds. Survival rate showed that 20% and 40% ipil-ipil leaves had the same result as of the pure commercial feeds.